Measurement of the production cross section for single top quarks in association with W bosons in proton-proton collisions at √s=13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Verlag, 2018)
A measurement is presented of the associated production of a single top quark and a W boson in proton-proton collisions at √ s = 13 TeV by the CMS Collaboration at the CERN LHC. The data collected corresponds to an integrated luminosity of 35.9 fb−1 . The measurement is performed using events with one electron and one muon in the final state along with at least one jet originated from a bottom quark. A multivariate discriminant, exploiting the kinematic properties of the events, is used to separate the signal from the dominant t¯t background. The measured cross section of 63.1 ± 1.8(stat) ± 6.4(syst) ± 2.1 (lumi) pb is in agreement with the standard model expectation